2002
DOI: 10.1016/s0736-0266(01)00060-2
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic protein‐1 induced bone formation in an infected segmental defect in the rat femur

Abstract: The goal of this study was to use a segmental defect model in the rat femur to determine if osteogenic protein-1 (OP-1) is capable of inducing bone formation in the presence of bacterial contamination. A 6 mni segmental defect was surgically created and stabilized with a polyacetyl plate and Kirschner wires in one femur in each of 126 Sprague-Dawley rats. The animals were divided into eight groups in which the defect was either left untreated, or subjected to various combinations of OP-l (1 I or 50 pg), lyophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
99
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 31 publications
0
99
1
2
Order By: Relevance
“…These controls may have shown that no bone formation occurs in the absence of MDR AB. Bone formation has not been observed in this model of infection without some form of osteogenic treatment [3][4][5]. One explanation could be that the newly formed bone may be the result of the presence of the absorbable collagen sponge used to retain the bacteria in the defect in the short term.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…These controls may have shown that no bone formation occurs in the absence of MDR AB. Bone formation has not been observed in this model of infection without some form of osteogenic treatment [3][4][5]. One explanation could be that the newly formed bone may be the result of the presence of the absorbable collagen sponge used to retain the bacteria in the defect in the short term.…”
Section: Discussionmentioning
confidence: 81%
“…One explanation could be that the newly formed bone may be the result of the presence of the absorbable collagen sponge used to retain the bacteria in the defect in the short term. However, the presence of the collagen sponge in an uninfected defect is not osteogenic: we chose this defect model because it is critical, meaning no bone forms unless an osteogenic treatment is applied [3][4][5]. Seventh, the virulence of SA was such that the polymicrobial experiments were not performed past 3 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The percentage increase in area of reparative callus with OP-1, compared with treatment groups without OP-1, did not necessarily translate into an equivalent percentage increase in torque to failure. Although our choices of the 25-lg dose of OP-1 and 4-week point initially seemed justified by the literature [4,15,18,21], our torsion failure testing results indicated the diabetic challenge in this model may have required a higher dose of OP-1 and longer followup to observe a difference in failure parameters. A time greater than 4 weeks may have allowed the callus to further remodel and become stronger.…”
Section: Discussionmentioning
confidence: 90%
“…Responding progenitor elements (stromal, periosteal, and perivascular cells) may retain their inductive response to BMPs, thereby overcoming an inhibitory environment [4]. Because BMP receptor II is downregulated in diabetes mellitus [33], it is possible treatment of a diabetic fracture with exogenous BMP may stimulate expression of BMP receptors [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation